Intestinal obstruction due to small bowel herniation through foramen of Winslow: a case report - Bandara, P. K. B. S. C. (J Med Case Rep, 2021)
BACKGROUND: Intestinal obstruction due to internal herniation of the bowel is a rare clinical entity which is often overlooked in the differential diagnosis of patients with abdominal pain who have no previous history of abdominal surgery. Several sites of bowel internal herniation have been described, amongst which internal herniation through the foramen of Winslow accounts for about 8% of cases. These patients present with nonspecific abdominal pain associated with symptoms of gastroesophageal reflux disease, and hence the diagnosis is often overlooked. The usual symptoms of intestinal obstruction can be delayed, which results in a delay in diagnosis and gangrene of the herniated bowel segment. Abdominal radiographs and computed tomography are helpful in the diagnosis. Open reduction is the management of choice; however, laparoscopic reduction has also been attempted, with good results. CASE PRESENTATION: We report a case of a middle-aged Sri Lankan man who presented with features of gastroesophageal reflux disease, developed features of intestinal obstruction and was found to have a gangrenous small bowel loop which had herniated through the foramen of Winslow. Following needle aspiration and reduction of the herniated small bowel loop, the gangrenous part of the small bowel was resected and an ileoileal anastomosis performed. The large foramen of Winslow was partially closed with interrupted stitches. The patient made an uneventful recovery. CONCLUSION: Since delayed diagnosis of bowel obstruction is detrimental, it is of utmost importance to diagnose it early. Because internal herniation of the small bowel through the foramen of Winslow presents with nonspecific symptoms including features of gastroesophageal reflux disease, as documented in several cases worldwide and also presented by our patient, there should be a high degree of suspicion of internal herniation of the bowel causing bowel obstruction and low threshold for extensive investigation of patients presenting with symptoms of gastroesophageal reflux disease which does not resolve with usual medication.